SAE Technical Paper Series 2012
DOI: 10.4271/2012-32-0019
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Plus Hydrogen as Fuel in a S.I. Engine: Experimental Results

Abstract: Storing hydrogen is one of the major problems concerning its utilization on board vehicles. Today hydrogen can be compressed and stored at 200 or 350 bar (it is foreseen that in a near future storage pressure will reach 700 bar, according to new expected regulations and using tanks in composite materials) or cryogenically liquefied. An alternative solution is storing hydrogen in the form of ammonia that is liquid at roughly 9 bar at environmental temperature and therefore involves relatively small masses and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…Ammonia combustion enhancement by in-situ NH3 dissociation was also investigated by Frigo et al [22][23][24] not in a CFR but in a commercial two-cylinder SI engine (CR = 10.7:1) equipped with a dedicated catalytic reformer. The stability of the whole system was proven for stoichiometric mixtures over a range of engine speeds and loads.…”
Section: Speciesmentioning
confidence: 97%
“…Ammonia combustion enhancement by in-situ NH3 dissociation was also investigated by Frigo et al [22][23][24] not in a CFR but in a commercial two-cylinder SI engine (CR = 10.7:1) equipped with a dedicated catalytic reformer. The stability of the whole system was proven for stoichiometric mixtures over a range of engine speeds and loads.…”
Section: Speciesmentioning
confidence: 97%
“…Liu et al [20] performed a numerical simulation on ammonia flame assuming the compression ratio of 15 conditions and investigated the laminar burning velocity and NO mole fraction in burned gas of ammonia flame. Recently, Frigo et al [21] investigated the applications of ammonia/hydrogen in an SI engine and showed that the possibility of improvement of engine brake thermal efficiency by the increase in compression ratio although the efficiency decreases with the increase in ammonia concentration in the fuel. Westlye et al [22] investigated the emission characteristics of an ammonia/ hydrogen engine in detail using an FT-IR analyzer and showed the difference of emission gas characteristics between an ammonia/hydrogen engine and a gasoline engine.…”
Section: Introductionmentioning
confidence: 98%
“…The application of ammonia in an actual combustor is also being studied. Frigo et al [6,7] applied hydrogen-doped ammonia as a fuel for the spark ignition engines. The power and thermal efficiencies of a hydrogen-doped ammonia fielded engine were compared with those of a gasoline engine.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the lower combustion intensities of ammonia, hydrogen-added ammonia flames have been studied [3][4][5][6][7]. Lee et al [3,4] experimentally investigated the laminar burning velocity of hydrogen-added ammonia/air premixed flames.…”
Section: Introductionmentioning
confidence: 99%